Comparison of mouse and human retinal morphology and function in albinism: potential implications for therapeutic development. (23rd February 2017) - Lee, Helena; Scott, Jennifer; Griffiths, Helen; Self, Jay E; Lotery, Andrew
Abstract: Background: Albinism is a disorder of melanin biosynthesis characterised by abnormal retinal development (foveal hypoplasia) and visual impairment, for which there are no effective treatments. Residual neural plasticity in the infant albino retina has previously been demonstrated. Therapeutic intervention during this developmental period has the potential to rescue visual function. Preclinical studies in murine albinism models are essential to develop novel therapeutics. We aimed to characterise retinal development, morphology, and function in the C57BL/6J-c2J null mouse model of oculocutaneous albinism (OCA), in preparation for future proof-of-concept treatment studies. Methods: We obtained 53 mixed cross-sectional and longitudinal in-vivo optical coherence tomography (2·2 μm axial resolution; Bioptigen, Morrisville, NC, USA) and electroretinography (Micron III; Phoenix, Pleasanton, CA, USA) examinations from nine C57BL/6J-c2J OCA mice at 4, 5, 6, 8, 12, and 16 weeks of age, which were compared with 110 examinations from 11 C57Bl/6J control mice. Retinal layer segmentation was performed with InVivoVue Diver 2.4 software (Bioptigen). Linear mixed regression modelling was used to analyse group differences. The results were then compared with published data on human albino retinal development, morphology, and function. Findings: In individuals with albinism, foveal hypoplasia is seen on optical coherence tomography, with the length of the photoreceptor outer segment correlating with visual acuity. Electroretingraphy responses are not affected. By contrast, although mice do not have foveae, we found significant reductions in the combined ganglion cell and inner plexiform layer (p=0·001) and retinal pigment epithelium (p<0·0001) thickness measurements, and also reductions in the length of the photoreceptor outer segment (p<0·0001) and end-tips (p=0·005) at 16 weeks of age in OCA mice. These findings corresponded with significant reductions in mean amplitudes on electroretingraphy in OCA mice compared with control mice (A-wave −98·3 μV [SD 62·9] vs −113 [66·5], p=0·028; B-wave 219·1 [90·1] vs 261·8 [98·9], p=0·003). Interpretation: We have identified several differences in using optical coherence tomography and electroretinography to monitor retinal morphology and function in human and mouse albinism. This finding is important for future translational studies and therapeutic development in albinism. Funding: Academy of Medical Sciences, Gift of Sight.